2020
DOI: 10.1002/ange.202012550
|View full text |Cite
|
Sign up to set email alerts
|

Activity and Stability Boosting of an Oxygen‐Vacancy‐Rich BiVO4 Photoanode by NiFe‐MOFs Thin Layer for Water Oxidation

Abstract: The introduction of oxygen vacancies (Ov) has been regarded as an effective method to enhance the catalytic performance of photoanodes in oxygen evolution reaction (OER). However,t heir stability under highly oxidizing environment is questionable but was rarely studied. Herein, NiFe-metal-organic framework (NiFe-MOFs) was conformally coated on oxygen-vacancy-richB iVO 4 (Ov-BiVO 4 )a st he protective layer and cocatalyst, forming ac ore-shell structure with caffeic acid as bridging agent. The as-synthesized Ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 56 publications
0
23
1
Order By: Relevance
“…Interestingly, the excellent applied bias photo-to-current efficiency (ABPE) of FeOOH/Ni-N 4 -O/BiVO 4 photoanode records 2.66% at 0.54 V vs RHE, which is 5.43 times higher than that of BiVO 4 (Figure e). This record ABPE of FeOOH/Ni-N 4 -O/BiVO 4 photoanode is higher than the reported values for BiVO 4 /FeOOH/NiOOH (1.75%), FeCoO x /BiVO 4 (1.16%), NiO/CoO x /BiVO 4 (1.5%), β-FeOOH/BiVO 4 (0.71%), PW 9 Co/BiVO 4 (0.84%), B-BiVO 4 (1.1%), CQDs/FeOOH/BiVO 4 (0.6%), NiFe-MOFs/O v -BiVO 4 (1.62%), Co 4 O 4 cubane/BiVO 4 (1.84%), Co@CB[5]/BiVO 4 (1.79%), Co-Pi/GCN/BiVO 4 (1.28%), Fe 2 O 3 /RGO/BiV 1– x Mo x O 4 (0.17%), etc. (Figure f).…”
Section: Resultscontrasting
confidence: 64%
“…Interestingly, the excellent applied bias photo-to-current efficiency (ABPE) of FeOOH/Ni-N 4 -O/BiVO 4 photoanode records 2.66% at 0.54 V vs RHE, which is 5.43 times higher than that of BiVO 4 (Figure e). This record ABPE of FeOOH/Ni-N 4 -O/BiVO 4 photoanode is higher than the reported values for BiVO 4 /FeOOH/NiOOH (1.75%), FeCoO x /BiVO 4 (1.16%), NiO/CoO x /BiVO 4 (1.5%), β-FeOOH/BiVO 4 (0.71%), PW 9 Co/BiVO 4 (0.84%), B-BiVO 4 (1.1%), CQDs/FeOOH/BiVO 4 (0.6%), NiFe-MOFs/O v -BiVO 4 (1.62%), Co 4 O 4 cubane/BiVO 4 (1.84%), Co@CB[5]/BiVO 4 (1.79%), Co-Pi/GCN/BiVO 4 (1.28%), Fe 2 O 3 /RGO/BiV 1– x Mo x O 4 (0.17%), etc. (Figure f).…”
Section: Resultscontrasting
confidence: 64%
“…As shown in Figure f, the ESR signal intensity at g = 2.002 for BiVO 4 /a-NiFeMo was much higher after CV treatment, demonstrating an increased unpaired electron trapped at the oxygen vacancies. Both the increased oxidation state of Ni and the increased ratio of O V and O OH could be attributed to the in situ formed oxy­(hydroxide) layer during the CV treatment, which was suggested to be the active species for the transition-metal-based catalyst with superior OER performance. It was also generally suggested that the increased density of oxygen vacancies facilitated the oxygen evolution reaction. , Therefore, the in situ activation of the BiVO 4 /a-NiFeMo photoanode was attributed to the rapid surface reconstruction of the surface-loaded a-NiFeMo cocatalyst during the CV treatment, which led to favorable electronic and geometric structure for higher OER performance.…”
Section: Resultsmentioning
confidence: 99%
“…57−60 It was also generally suggested that the increased density of oxygen vacancies facilitated the oxygen evolution reaction. 61,62 Therefore, the in situ activation of the BiVO 4 /a-NiFeMo photoanode was attributed to the rapid surface reconstruction of the surface-loaded a-NiFeMo cocatalyst during the CV treatment, which led to favorable electronic and geometric structure for higher OER performance. The effect of the in situ activation process can be quantitively illustrated by comparing the electrochemical active surface area (ECSA) of the BiVO 4 /a-NiFeMo photoanode before and after CV treatment.…”
Section: Resultsmentioning
confidence: 99%
“…(3) constructing heterostructures or core-shell structure [331]; (4) ultraviolet light-induced regeneration [332].…”
Section: Summary Challenges and Future Perspectives In Defect-engineered N 2 Photocatalysismentioning
confidence: 99%